Risk factors for major low anterior resection syndrome: meta-analysis and systematic literature review - Evgeny A. Khomyakov; Islam O. Nafedzov; Oksana Y. Fomenko; Mikhail V. Alekseyev; Sergey A. Frolov; Stanislav V. Tchernyshov; Evgeny G. Rybakov (Russian Open Medical Journal)
Introduction — Low anterior resection syndrome (LARS) is a socially significant problem that impedes social adaptation and contributes to deterioration of life quality in patients. The objective of this study was to search for the category of patients most prone to major LARS, as well as to identify the factors determining the severity of this syndrome manifestations. Material and Methods — Systematic review and meta-analysis were performed according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The study selected publications that included the functional results of treatment of patients operated for rectal cancer. Functional impairments were assessed according to the international LARS Score. Statistical analysis was performed using the inverse-variance weighted average method (IVW) with calculation of the odds ratio logarithm and standard error of the mean. Results — After a critical search and analysis of all literature sources, eight studies were found suitable for meta-analysis. In total, 1042 patients (796 men and 246 women) were included into statistical analysis, 409 of which (39.2%) had symptoms of major LARS. Chemotherapy was performed on 637 (62.5%) patients, while 568 subjects (55.5%) underwent radiation therapy, and anastomotic leaks were described in 89 (8.5%) people. According to the results of the meta-analysis, statistically significant factors were: preventative ostomy (OR=3.32, 95% CI 1.99-5.55, p<0.00001), chemotherapy (OR=1.98, 95% CI 1.23-3, 19, p=0.005), radiation therapy (OR=5.00, 95% CI 2.73-9.13, p <0.00001), anastomotic leaks (OR=2.93, 95% CI 2.30-3, 73, p<0.00001), anal verge distance from anastomosis site (OR=2.61, 95% CI 1.47-4.62, p=0.001). Conclusion — The results of our meta-analysis allowed us identifying the group of rectal cancer patients most vulnerable to LARS. The risk of developing severe functional disorders is significantly higher in patients with low colorectal anastomosis, as well as in patients undergoing neoadjuvant radiation therapy.